2018
DOI: 10.1016/j.jvoice.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal Dystonia Mimicking Spasmodic Dysphonia

Abstract: PD, or dystonia with predominant pharyngeal involvement, is a rare entity with vocal manifestations that are not well described. It can be easily mistaken for spasmodic dysphonia. PD is specific to speech-related tasks. A novel method of BTX injections into the involved muscles results in a significant improvement in voice without significant dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…2 In addition, dystonia-related swallowing difficulties typically correspond to pharyngeal dystonia, which is not scored in the GDRS but often linked with laryngeal dystonia. [12][13][14] Results…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In addition, dystonia-related swallowing difficulties typically correspond to pharyngeal dystonia, which is not scored in the GDRS but often linked with laryngeal dystonia. [12][13][14] Results…”
Section: Discussionmentioning
confidence: 99%
“…However, this BFM item was compared only with the larynx score of the GDRS, because laryngeal dystonia is more common than oromandibular dystonia 2 . In addition, dystonia‐related swallowing difficulties typically correspond to pharyngeal dystonia, which is not scored in the GDRS but often linked with laryngeal dystonia 12–14 …”
Section: Methodsmentioning
confidence: 99%
“…However, dystonia localized only in the pharyngeal muscle is extremely rare, and its pathogenesis is unclear and scarcely reported. Some studies have reported dysphonia and dysphagia due to pharyngeal dystonia, but a treatment strategy has not yet been established [6].…”
mentioning
confidence: 99%